Cause and effect : performance attribution in commercial real estate - Furfine, Craig (London : Kellogg School of Management, 2017)
In April 2015, Shannon Enberg, Managing Director of Real Assets at the United Kingdom Telecom and Technology Pension Scheme (UKTTPS), received a startling memo from the fund's board of directors. In a nutshell, the board sought to reduce the fund's multimillion-pound annual expenditure on management fees by asking all managing directors to drastically cut the number of private managers being used to manage UKTTPS assets. Enberg was told to cut the number of her external managers in half, but given the illiquidity of her private equity investments in commercial property, she would be allowed to make the decision to rehire each manager (or not) as each of her investments matured. UKTTPS had two investments in closed-end property funds that had just liquidated their final holdings at the end of 2014. Both managers had new funds being raised that could recycle the investment proceeds, but now that she was being forced to cut back, Enberg wondered whether either was really worth rehiring.
Originally published in Furfine, C. (2017). Cause and effect: Performance attribution in commercial real estate. 5-315-308. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Portfolio management; Investment analysis; Commercial real estate